О сезонности размножения пятнистых оленей (Cervus nippon hortulorum Sw.) в условиях юга Украины - Стекленев, Е.П. (Вестник зоологии, 1978)
Reproductive power of Cervus nippon hortulorum Sw. is studied in connection with their acclimatization under conditions of the Ukraine South. It is determined that sexual activity season in C. nippon hortulorum is considerably widened with the maximum number of fruitful matings (about 80%) in October-November and birth of offspring in May-June. Normal sexual cycles in mature females proceed in the autumn-winter period and coincide with spermatogenesis in mature males. Growth, development and shedding of horns regulated by concentration of testosterone (sex hormone) in animals' blood are external morphological characters of sexual activity of males.